MEDIATION SKILLS IN THE ENGLISH LANGUAGE CLASSROOM (Multidisciplinary Journal of Science and Technology, 2024)
Mediation skills are essential for fostering effective communication, understanding, and conflict resolution in the English language classroom. These skills facilitate a collaborative learning environment, enhance student engagement, and support language acquisition. This article explores the importance of mediation skills, strategies for integrating them into language teaching, and their impact on students' language proficiency and interpersonal skills. Practical recommendations for educators are provided to help develop mediation competencies in students, promoting a more inclusive and effective language learning experience.